Baseline patient‐reported outcomes from UNITE: an observational, international, multicentre registry to evaluate hidradenitis suppurativa in clinical practice. (1st March 2020) - Kimball, A.B.; Crowley, J.J.; Papp, K.; Calimlim, B.; Duan, Y.; Fleischer, A.B.; Sobell, J.
Abstract: Background: Hidradenitis suppurativa (HS) is a chronic, inflammatory, skin condition associated with many comorbidities and often has a substantial impact on patients' lives. Objectives: To evaluate symptom burden and health‐related quality of life (HRQoL) at baseline in patients with HS in an observational, real‐world, clinical setting using several tools including a validated HS‐specific instrument. Methods: This study evaluated HRQoL data from the international UNITE HS disease registry. Administration of patient‐reported outcome (PRO) instruments and collection of data were executed per local regulations. All data were assessed using descriptive statistical methods. Results: PRO data from 529 adults and 65 adolescents were evaluated. Most adults (64.5%) and adolescents (73.8%) were classified as Hurley Stage II with substantial disease burden at baseline. HS had a large effect (mean DLQI = 12.6) and moderate effect (mean CDLQI = 6.9) on the lives of adults and adolescents, respectively. Approximately 58% of adults and 41% of adolescents had anxiety scores beyond the normal range; 30% of adults and 16% of adolescents exhibited symptoms of depression. Based on HSSA and HSIA scores, approximately 30% of adults reported a substantial burden of multiple HS clinical symptoms and more than 45% reported a significant emotional impact of HS that adversely affected their intimate relationships. Only 60% of adults were employed and of those, 64% reported at least some degree of impairment while working because of HS. Conclusions: Based on PROs collected from patients enrolled in the UNITE registry, a real‐world, clinical setting, HS has a significant negative impact on the everyday lives of patients affected by this disease.